A Study of the Relationship Between Nurses’ Professional Self-Concept and Professional Ethics in Hospitals Affiliated to Jahrom University of Medical Sciences, Iran - Parandavar, Nehleh (Glob J Health Sci, 2016)
BACKGROUND: Commitment to ethics usually results in nurses’ better professional performance and advancement. Professional self-concept of nurses refers to their information and beliefs about their roles, values, and behaviors. The objective of this study is to analyze the relationship between nurses’ professional self-concept and professional ethics in hospitals affiliated to Jahrom University of Medical Sciences. METHODS: This cross sectional-analytical study was conducted in 2014. The 270 participants were practicing nurses and head-nurses at the teaching hospitals of Peimanieh and Motahari in Jahrom University of Medical Science. Sampling was based on sencus method. Data was collected using Cowin's Nurses’ self-concept questionnaire (NSCQ) and the researcher-made questionnaire of professional ethics. RESULTS: The average of the sample's professional self-concept score was 6.48±0.03 out of 8. The average of the sample's commitment to professional ethics score was 4.08±0.08 out of 5. Based on Pearson's correlation test, there is a significant relationship between professional ethics and professional self-concept (P=0.01, r=0.16). CONCLUSION: In view of the correlation between professional self-concept and professional ethics, it is recommended that nurses’ self-concept, which can boost their commitment to ethics, be given more consideration.